The dynamic change of propagation from meteorological drought to hydrological drought at the basin scale: A case study from the Weihe River Basin, China - Zhao, Panpan; Xie, Bingbo; Huang, Xudong; Qu, Bo (Frontiers in Environmental Science, 2022)
Current climate change has led to frequent drought events in the Weihe River Basin, and the risks and impacts of drought are becoming increasingly severe. In order to study meteorological drought and hydrological drought at different scales and the propagation of drought between them, in this study, meteorological and hydrological drought conditions were calculated for 3-, 6-, 9-, and 12-month timescales based on 56 years of monthly precipitation and monthly runoff data of the Weihe River Basin using the Standardized Precipitation Index (SPI) and the Streamflow Drought Index (SDI), respectively. We explore analyzing the differences between them and their relationship and establishing regression equations based on the relationship and the dynamic propagation time of meteorological and hydrological droughts at different timescales. The results demonstrate that 1) the frequencies of both meteorological and hydrological droughts have shown an increasing trend in the last 56 years; 2) the relationship between meteorological drought and hydrological drought varied over time; 3) according to dynamic change analysis, propagation time tends to be shorter on the 3-month timescale and longer on the 6-month, 9-month, and 12-month timescales; and 4) the accelerated propagation time between meteorological drought and hydrological drought may be related to the increase in precipitation and temperature. The findings not only provide scientific support for the formulation of drought prevention and disaster reduction strategies in this basin but also have important scientific and practical application value.